Supervision by the Financial Services Authority on Investment-Based Life Insurance (Unit Link) - Rizky Noor Fajrina; Waspiah Waspiah (Universitas Negeri Semarang, 2021)
Problems with unit-linked life insurance products such as product transparency where the agent does not provide a detailed explanation regarding the characteristics, benefits, risks, and costs of unit-linked life insurance. This study aims to describe the protection of unit link life insurance in Indonesia and the supervision of the Financial Services Authority, the constraints faced and the steps that must be taken so that the insurance business can run well. This study uses a qualitative, sociological juridical approach. Primary data sources were taken by interview, observation, and documentation. While secondary data obtained from legislation, books, journals, scientific articles related to research. The results showed that: (1) The protection of the unit link life insured in Indonesia is not yet in accordance with the existing regulations. Life insurance agents who violate Marketers Standards of Practice and Code of Conduct may be subject to sanctions. Preventive and repressive efforts are carried out by the Financial Services Authority in order to protect the insured. (2) Supervision of the Financial Services Authority in the insurance business is microprudential supervision which, by its nature, is divided into prudential supervision and market conduct supervision. The conclusions in this study: (1) The protection of life insurance for unit link in Indonesia is not yet fully in accordance with the applicable regulations, this is due to several life insurance agents that do not meet the applicable rules.